Network pharmacology integrated with experimental validation reveals the regulatory mechanism of action of Hehuan Yin decoction in polycystic ovary syndrome with insulin resistance. (10th May 2022) - Wu, Yuan-Yuan; Li, Shu-Yu; Zhu, Hui-Qing; Zhuang, Zi-Ming; Shao, Meng; Chen, Fei-Long; Liu, Chang-Shun; Tang, Qing-Fa
Abstract: Ethnopharmacological relevance: Hehuan Yin decoction (HHY), first recorded in the Jingyue Quanshu (published in 1624 A.D.), is composed of Albizia julibrissin Durazz. and Ampelopsis japonica (Thunb.) Makino. Aim of the study: This study aimed to investigate the mechanism of action of HHY in treating polycystic ovary syndrome with insulin resistance (PCOS-IR). Materials and methods: Network pharmacology and molecular docking were used to predict active compounds, potential targets, and pathways for PCOS-IR treatment using HHY. Female Sprague–Dawley rats were administered letrozole (1 mg/kg) with a high-fat diet to establish a PCOS-IR model. Thereafter, symptoms, ovarian pathology, serum insulin resistance, and sex hormone levels were determined. Western blotting was used to determine the levels of PI3Kp85α, AKT, phospho (p)-AKT, and GSK3β in the ovaries of rats. Results: Network pharmacology revealed 58 components in HHY and 182 potential targets that were shared between HHY and PCOS-IR. HHY could potentially treat PCOS-IR via the insulin resistance, PI3K/AKT, HIF-1, and steroid hormone biosynthesis pathways. Molecular docking revealed that PI3K, AKT1, GSK3β, IRS1, and EGFR had high affinities to HHY compounds. In the PCOS-IR rats, HHY significantly normalised the symptoms and ovarian pathology, increased follicle-stimulating hormone (FSH) and oestradiol levels in the serum, and decreased the levels of fasting plasma glucose and fasting insulin, as well as the insulin resistance index. HHY also decreased the luteinising hormone (LH) and testosterone levels and the LH/FSH ratio in the PCOS-IR rats and increased the levels of PI3K, p-AKT, and GSK3β in ovary tissue, which indicated the activation of the PI3K/AKT pathway. Conclusions: HHY can improve PCOS-IR symptoms via multiple pharmacological pathways and may be a potential alternative therapy for the treatment of PCOS-IR. Graphical abstract: Image 1 Highlights: The mechanisms of HHY on PCOS-IR was predicted by network pharmacology and molecular docking. Animal investigations verify that HHY can alleviated PCOS-IR symptoms and its mechanism is through PI3K/AKT pathway. Ancient prescription HehuanYin (HHY) can effectively treat PCOS with insulin resistance.